Enhancement of the Adsorptive Properties of a Desert Salsola Vermiculata Species - Noureddine Benderdouche; Benaouda Bestani; Baghdad Benstaali; Zoubir Derriche (Adsorption Science & Technology)
Heat pretreatment, steam activation and 20% phosphoric acid activation were found to enhance the adsorption capacity of a desert Salsola Vermiculata plant species significantly relative to the inactivated plant and powdered wood carbon 600200 EX 694 as obtained from Belgium. The batch adsorption experiments resulted in a maximum adsorption capacity determined from Langmuir models of up to 476 mg/g for acetic acid, 238 mg/g for copper(II) ions and 144 mg/g for nickel(II) ions, whereas for the inactivated plant they attained values of 53 mg/g, 65 mg/g and 18 mg/g, respectively. The results for the wood carbon were 65 mg/g for acetic acid, 45 mg/g for copper(II) ions and 2.4 mg/g for nickel(II) ions. The Freundlich model was found to provide a better description of copper(II) ion adsorption onto the steam- and chemically-activated plant, whereas nickel(II) ion adsorption processes followed Langmuir behaviour. These results showed that the activated plant could prove to be very useful in removing toxic substances from wastewater.